y2p2 -3xy+y=0
WE HAVE TO SOLVE THE D.E. GIVEN ABOVE .
SOLUTION:-
"y^2p^2-3xy+y=0\\\\\\implies\\sqrt y p-\\sqrt {(3x-1)}=0\\\\\\implies\\sqrt y\\frac{dy}{dx}-\\sqrt{(3x-1)}=0\\\\\\implies\\int\\sqrt ydy-\\int\\sqrt {(3x-1)}dx=0\\\\\\implies\\frac{2}{3}y^\\frac{3}{2}-\\frac{2}{9}(3x-1)^\\frac{3}{2}=c'\\\\\n [c' \\; is \\; a \\;constant]\\\\\n\\implies3y^\\frac{3}{2}-(3x-1)^\\frac{3}{2}=c\\\\\n[c=9c'\/2]"
Hence the solution of the given equation:
"\\boxed{\\pmb{3y^\\frac{3}{2}-(3x-1)^\\frac{3}{2}=c}}"
Comments
Leave a comment